Application of meta-transcriptomics and –proteomics to analysis of in situ physiological state - Konopka, Allan; Wilkins, Michael (Frontiers in Microbiology, 2012)
Analysis of the growth-limiting factor or environmental stressors affecting microbes in situ is of fundamental importance but analytically difficult. Microbes can reduce in situ limiting nutrient concentrations to sub-micromolar levels, and contaminated ecosystems may contain multiple stressors. The patterns of gene or protein expression by microbes in nature can be used to infer growth limitations, because they are regulated in response to environmental conditions. Experimental studies under controlled conditions in the laboratory provide the physiological underpinnings for developing these physiological indicators. Although regulatory networks may differ among specific microbes, there are some broad principles that can be applied, related to limiting nutrient acquisition, resource allocation, and stress responses. As technologies for transcriptomics and proteomics mature, the capacity to apply these approaches to complex microbial communities will accelerate. In particular, global proteomics reflect expressed catalytic activities. Furthermore, the high mass accuracy of some proteomic approaches allows mapping back to specific microbial strains. For example, at the Rifle IFRC field site in Western Colorado, the physiological status of Fe(III)-reducing populations has been tracked over time. Members of a “subsurface clade” within the Geobacter predominated during carbon amendment to the subsurface environment. At the functional level, proteomic identifications produced inferences regarding (i) temporal changes in anabolism and catabolism of acetate, (ii) the onset of N2 fixation when N became limiting, and (iii) expression of phosphate transporters during periods of intense growth. The application of these approaches in situ can lead to discovery of novel physiological adaptations.